The Role of Saudi Television in processing Intellectual Security Issues of Saudi Youth - Al-Maliki, Mashaal Ahmed Hamed (Journal of Humanities & Social Sciences, 2019)
This study aimed to identify the role of Saudi TV in processing intellectual security issues of Saudi youth and recognize its role in promoting national and Islamic affiliation، the field descriptive approach was used، and the researcher used the questionnaire tool that was applied to a sample of (481) young students of King Abdulaziz University to achieve the study‘s aims. The study emphasized that Saudi TV is the most important source on which Saudi youth rely on gathering information about intellectual security issues with an average of (2.05)، followed by Arab satellite channels with an average of (1.78) and a medium reliance rating. The results showed that the cognitive effects of youth exposure to intellectual security programs on Saudi TV were at the average of (2.15) and standard deviation (0.62). And that the emotional effects of youth exposure to intellectual security programs on Saudi TV are medium، with an average of (2.33) and a standard deviation of (0.65). The results also showed a statistically significant positive correlation between the degree of Saudi youth’s dependence on Saudi TV programs in addressing intellectual security issues and the extent of exposure to them. There were differences of statistical significance in the intensity of the exposure of Saudi youth to the issues of intellectual security in Saudi TV according to their demographic variables، which was partially proven in the variables (gender and age) and was not proven in the variable of education.